Identification of cross-equatorial northerly surge (CENS) relationship to very heavy rain events in Jakarta - Lestari, Tri Anggun; Athallah, M. Syauqi B.; Haryanto, Yosafat D. (Bulletin of Applied Mathematics and Mathematics Education, 2023)
CENS is a meteorological phenomenon in the form of surface wind flow originating from the South China Sea (SCS), very strongly across the equator. CENS is closely related to the increase in average rainfall in parts of Indonesia. There has been very heavy rainfall on January 18, 2022 in the Jakarta area which resulted in flooding. Therefore, this study focuses on seeing if there is a CENS relationship that is factor in increasing rainfall in the Jakarta area on January 18, 2022. The results showed that the NCS began to form on January 16-17, 2022 with a Siberian High of 1040.6 hPa and the propagation of cold air masses from Asia to the south which was an indicator of CENS. The next day, the CENS phenomenon began to occur, characterized by meridional wind speeds in the 105˚- 115˚BT region of less than -5 m/s. This phenomenon triggers the strengthening of the northeast Asian monsoon flow so that the area south of the equator, including Jakarta, gets a large moisture transport from the SCS. This causes the potential for the formation of high convective clouds to trigger very heavy rain and cause flooding in the Jakarta area on January 18, 2022.